2020
DOI: 10.1111/ceo.13861
|View full text |Cite
|
Sign up to set email alerts
|

Microdroplet and spatter contamination during phacoemulsification cataract surgery in the era of COVID‐19

Abstract: Importance Determine phacoemulsification cataract surgery risk in a Covid‐19 era. Background SARS‐CoV‐2 (Covid‐19) transmission via microdroplet and aerosol generating procedures present a risk to medical professionals. As the most common elective surgical procedure performed globally; determining contamination risk from phacoemulsification cataract surgery may guide personal protection equipment use. Design Pilot study involving phacoemulsif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…Although SARS‐CoV‐2 has been identified in tears, it is not clear whether these viral particles are infectious 8,9 . Phacoemulsification cataract surgery is a recognized cause of droplet generation, 14 but the evidence on aerosolization is mixed. McGhee et al 14 demonstrate that despite droplet formation, spread to the surgeon appears to be low and phacoemulsification surgery is probably safe using standard surgical precautions.…”
mentioning
confidence: 99%
“…Although SARS‐CoV‐2 has been identified in tears, it is not clear whether these viral particles are infectious 8,9 . Phacoemulsification cataract surgery is a recognized cause of droplet generation, 14 but the evidence on aerosolization is mixed. McGhee et al 14 demonstrate that despite droplet formation, spread to the surgeon appears to be low and phacoemulsification surgery is probably safe using standard surgical precautions.…”
mentioning
confidence: 99%
“…They are summarized briefly in Table 1. Simulations in the ophthalmic office and operating theatre have suggested that these measures significantly decrease the likelihood of SARS‐CoV‐2 infection in ophthalmology practice 125‐129 …”
Section: Implications For the Ophthalmologistmentioning
confidence: 99%
“…Absence of evidence does not mean evidence of absence, so studies such as that by McGhee et al 9 are needed to build our scientific evidence base and allow sensible conclusions regarding theoretical viral transmission from surgery. One extrapolation from the data presented by McGhee et al is that standard personal protection equipment (PPE)—surgical gown, gloves and mask—appear to provide adequate protection from droplets for those closest to the phacoemulsifier.…”
mentioning
confidence: 99%
“…In terms of protecting surgeons and other operating theatre staff from exposure to possible infection from the patient for SARS‐CoV‐2, our focus should remain on our systems for mitigating the far more likely respiratory and droplet transmission, using the assumption that any patient may be a source of transmission 7,8 . However, evidence like that presented by McGhee et al 9 will help us learn to protect surgeons and others in the operating theatre from potential infective material produced by our most common surgical procedure.…”
mentioning
confidence: 99%
See 1 more Smart Citation